Best dives Cayman Islands - Huber, Joyce (Hunter travel guides., 2009)
Based on the classic Best Dives of the Caribbean, this publication focuses on the Cayman Islands alone. Includes the latest and best dive and snorkel sites, each rated for visual excellence and marine life. The author's knowledge of the Caribbean sites is